Advances in Metabolic Engineering of Saccharomyces cerevisiae for Cocoa Butter Equivalent Production - Wang, Mengge; Wei, Yongjun; Ji, Boyang; Nielsen, Jens (Frontiers in Bioengineering and Biotechnology, 2020)
Cocoa butter is extracted from cocoa beans, and it is mainly used as raw material for the production of chocolate and cosmetics. Increased demands and insufficient cocoa plants led to a shortage of cocoa butter supply, and there is therefore much interesting in finding an alternative cocoa butter supply. However, the most valuable component of cocoa butter is rarely available in other vegetable oils. Saccharomyces cerevisiae is an important industrial host for production of chemicals, enzyme and pharmaceuticals. Advances in synthetical biology and metabolic engineering had enabled high-level of TAGs production in yeast, which provided possible solutions for cocoa butter equivalents (CBEs) production. Diverse engineering strategies focused on the fatty acid-producing pathway had been applied in S. cerevisiae, and the key enzymes determining the TAG structure were considered as the main engineering targets. Recent development in phytomics and multi-omics technologies provided clues to identify potential targeted enzymes, which are responsible for CBE production. In this review, we have summarized recent progress in identification of the key plant enzymes for CBE production, and discussed recent and future metabolic engineering and synthetic biology strategies for increased CBE production in S. cerevisiae.